2021
DOI: 10.3389/fpls.2021.632464
|View full text |Cite
|
Sign up to set email alerts
|

Higher Elevations Tend to Have Higher Proportion of Plant Species With Glandular Trichomes

Abstract: Glandular trichomes are well known to participate in plant chemical and physical defenses against herbivores, especially herbivorous insects. However, little is known about large-scale geographical patterns in glandular trichome occurrence. Herbivory pressure is thought to be higher at low elevations because of warmer and more stable climates. We therefore predicted a higher proportion of species with glandular trichomes at low elevations than at higher elevations. We compiled glandular trichome data (presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Although we do not have evidence for V. incana being a long-time resident of the Altai Mountainsit is widespread from eastern Europe to eastern Asia, V. porphyriana is a subalpine species, restricted to the Altai Mountains and certainly originated from V. spicata as a form adapted to subalpine habitat (Elenevsky, 1971). In fact, V. porphyriana differs from V. spicata mainly in the strongly glandular indumentum (Kosachev & al., 2013), which is a general phenomenon in alpine plants (Wu & al., 2021). Thus, after the ice ages it is easily imaginable that V. porphyriana extended its range upwards followed by the widespread, lowland V. longifolia, V. pinnata and V. spicata migrating to the Pleistocene refugia of V. porphyriana and then crossing with it.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we do not have evidence for V. incana being a long-time resident of the Altai Mountainsit is widespread from eastern Europe to eastern Asia, V. porphyriana is a subalpine species, restricted to the Altai Mountains and certainly originated from V. spicata as a form adapted to subalpine habitat (Elenevsky, 1971). In fact, V. porphyriana differs from V. spicata mainly in the strongly glandular indumentum (Kosachev & al., 2013), which is a general phenomenon in alpine plants (Wu & al., 2021). Thus, after the ice ages it is easily imaginable that V. porphyriana extended its range upwards followed by the widespread, lowland V. longifolia, V. pinnata and V. spicata migrating to the Pleistocene refugia of V. porphyriana and then crossing with it.…”
Section: ■ Discussionmentioning
confidence: 99%
“…porphyriana differs from V . spicata mainly in the strongly glandular indumentum (Kosachev & al., 2013), which is a general phenomenon in alpine plants (Wu & al., 2021). Thus, after the ice ages it is easily imaginable that V .…”
Section: Discussionmentioning
confidence: 99%
“…Although caffeine, flavonoids, and other bitter molecules found in coffee are not known to be cytotoxic in plants, flavonoids are thought to have antifungal properties (Galeotti et al, 2008) , while caffeine is known to protect plants against predation by insects and other herbivores, as well as infection by bacteria and fungi (Baumann & Gabriel, 1984;Frischknecht et al, 1986;Mohammed & Al-Bayati, 2009;Nathanson, 1984) . Given that stresses from herbivory and bacterial and fungal colonization are thought to be reduced at lower temperatures and thus higher altitudes (Desaint et al, 2021;Wu et al, 2021) , bitter antimicrobial and anti-herbivory compounds may not be necessary in high concentrations at such altitudes and could be repurposed for alternative functions, thereby potentially explaining the adaptive value of the postulated selective breakdown of caffeine and flavonoids by high-altitude C. arabica. Although this preliminary postulation is interesting, it remains uncertain whether heighted EF1-𝛾 expression is a property of all high-altitude cultivars of C. arabica or only the RS cultivar being investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of elevation in the development and expression of plant defenses remains controversial, with certain studies finding positive correlations between elevation and plant defense and others reporting the opposite. Wu et al speculate that these inconsistent findings are likely due to other elevation-dependent abiotic factors such as temperature, rather than elevation itself (R. Wu et al, 2021). Interestingly, Cheng et al identified that A. thaliana increases ETI signalling at temperatures ranging from 10°C to 23°C, but shifts to increasing pattern-triggered immunity (PTI) at temperatures ranging from 23°C to 32°C.…”
Section: Discussionmentioning
confidence: 99%
“…are efficient defense molecules against insect herbivores (Tosovic, 2017;Kundu and Vadassery, 2019;Punia et al, 2021). The abundance as well as the species richness of herbivorous Orthoptera decreased with elevation in the Central Alps (Pitteloud et al, 2020), and the highest species richness of insect herbivores was reported at elevations between 2,000 and 3,000 masl, in Hengduan Mountains in southwestern China (Wu et al, 2021). The decrease in herbivorous insects will also decrease herbivory pressure along elevation gradients; this should lead to an overall reduction in plant defenses or a lower level of plant resistance at high elevations (Pellissier et al, 2012).…”
Section: Discussionmentioning
confidence: 99%